THE INFLUENCE OF WORK DISCIPLINE, COMMUNICATION AND CONFLICT TO WORK ON EMPLOYEES PERFORMANCE AT PT PRATAMA MAKMUR JAYA MEDAN - Tamara, Shelly; Mirza, Deni Faisal; Wijaya, Willy Evan; Kosasih, Desy (International Journal of Social Science and Business, 2021)
This study aims to test and analyze the influence of Work Discipline, Communication and Conflict to Work on the Performance of Employees of PT Pratama Makmur Jaya Medan. The research method is quantitative approach, type of research is descriptive and quantitative nature of this research is descriptive explanatory. Methods of data analysis is multiple linear regression analysis. Sample collection techniques, namely simple random sampling. The research sample is 106 employees. The test results obtained the discipline of work, communication and conflict has positive and significant effect simultaneously on the performance of employees at PT Pratama Makmur Jaya MedanÂ This study aims to test and analyze the influence of Work Discipline, Communication and Conflict to Work on the Performance of Employees of PT Pratama Makmur Jaya Medan. The research method is quantitative approach, type of research is descriptive and quantitative nature of this research is descriptive explanatory. Methods of data analysis is multiple linear regression analysis. Sample collection techniques, namely simple random sampling. The research sample is 106 employees. The test results obtained the discipline of work, communication and conflict has positive and significant effect simultaneously on the performance of employees at PT Pratama Makmur Jaya MedanWork Discipline, Communication, Work Conflicts, EmployeePerformance Â